EP.TU.200Improving variable rate insulin infusion compliance in general surgery. (28th October 2021) - George, Jayan; Jackson, Samuel; Orsi, Andrew; Ardley, Rohan
Abstract: Aims: 1. Audit the current variable rate insulin infusion (VRII) practice per local guidelines. 2. Understand barriers to good VRII practice to create an intervention. 3. Re-Audit the VRII practice following intervention. Methods: Junior doctors were surveyed using Likert scales (1 to 5: not at all confident to very confident) as well as closed and open questions. Chain action reaction (CAR) theory was used. Six domains were identified against a local proforma. Initial audit and questionnaire were collected from November 2019 to January 2020 and analysed using Microsoft Excel. Intervention consisted of a condensed one-page algorithm with group teaching. Re-audit data was collected between June 2020 to August 2020 for comparison. Results: Questionnaire – 53.6% (15/28) of juniors responded. Challenges included conversion oral hypoglycaemics and complexity of the guidance. Group teaching and a condensed portable format were the most popular modalities for delivery of further education. Initial Audit – 12 VRII charts were audited. 33.3% (4/12) were completed correctly. Areas of significant need for improvement were as follows: ensuring long-acting insulin is prescribed, transferring from a VRII back to oral medications and appropriate fluid prescribing. Re-Audit – 18 charts were audited following intervention. Of these, 66.7% (12/18) were completed correctly. There was a significant improvement in appropriate fluid prescribing and long-acting insulin prescriptions. Conclusions: Understanding the factors involved throughout the chain of how VRIIs are prescribed has helped to implement a positive intervention in our department. The improvement has been significant (100% better) however there is still further work required to improve compliance.